2019
DOI: 10.1108/sbm-10-2018-0092
|View full text |Cite
|
Sign up to set email alerts
|

Rural community well-being through minor league sport

Abstract: Purpose The purpose of this paper is to investigate how small-town residents’ perceptions of a minor league sport team’s socially responsible initiatives (SRI) influence several psychological responses to SRI, including feelings of gratitude, subjective well-being, place attachment and community pride. Design/methodology/approach A cross-sectional, survey-based research design was employed to empirically assess the effects of SRI on positive psychological responses in the context of a minor league sport team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
(68 reference statements)
0
3
0
1
Order By: Relevance
“…Es así como, las organizaciones deportivas debido a su carácter social, sirven como plataforma de transformación en pro del desarrollo humano, generan aportes a la economía y al bienestar de las personas y llevan a cabo acciones filantrópicas y benéficas para fomentar la conciencia social (Babiak, 2010;Giulianotti, 2011;Heinze et al, 2014;Kim et al, 2019). Por otra parte, los equipos deportivos son un referente en procesos de planificación y enseñanza para las nuevas generaciones e involucran jugadores apasionados por lo que hacen (Babiak & Wolfe, 2009).…”
Section: El Deporte Como Herramienta De Responsabilidad Socialunclassified
“…Es así como, las organizaciones deportivas debido a su carácter social, sirven como plataforma de transformación en pro del desarrollo humano, generan aportes a la economía y al bienestar de las personas y llevan a cabo acciones filantrópicas y benéficas para fomentar la conciencia social (Babiak, 2010;Giulianotti, 2011;Heinze et al, 2014;Kim et al, 2019). Por otra parte, los equipos deportivos son un referente en procesos de planificación y enseñanza para las nuevas generaciones e involucran jugadores apasionados por lo que hacen (Babiak & Wolfe, 2009).…”
Section: El Deporte Como Herramienta De Responsabilidad Socialunclassified
“…The relationship between residents' perceptions of event impacts and their well-being has been of concern to tourism scholars (Al-Emadi et al, 2017;Kaplanidou et al, 2013;Y. D. Kim, Magnesen, et al, 2019;Lin et al, 2017).…”
Section: Impact Of Mega Events and Residents' Psychological Well-beinmentioning
confidence: 99%
“…Scholars have also accumulated evidence that socio-cultural impacts can contribute to residents' well-being. Y. D. Kim, Magnesen, et al (2019), for example, found that residents who perceive the impact of local sport team's contributions to community welfare (i.e. social impact) were more likely to feel grateful and experience greater well-being.…”
Section: Impact Of Mega Events and Residents' Psychological Well-beinmentioning
confidence: 99%
“…Beyond economic analyses, some scholars have focused on the potential social impacts that a sport event may have on a local community (Oja et al , 2018). Some benefits that have been explored include civic pride (Baade and Matheson, 2016), psychic income (Crompton, 2004) and well-being and attachment (Kim et al , 2019). Other researchers have investigated the potential of sport organizations to act as a social anchor within a community (Alonso and O'Shea, 2012).…”
Section: Introductionmentioning
confidence: 99%